Literasi Keuangan dan Legalisasi Usaha Sebagai Strategi Peningkatan Akses Permodalan bagi UMKM - Abbas, Muchlis; idrus, arnida; Meda, Tamrin; Sabrida, Sabrida (ADPERTISI, 2025)
The implementation of this Community Service aims to increase access to capital for MSMEs in North Galesung, Takalar Regency, through financial literacy and business legalization. The main problem for MSMEs in this region is capital barriers due to lack of financial understanding and the absence of legality. The activity was carried out with an educational-participatory approach. The results showed a significant increase in financial literacy (the score increased by 48.3%) and the success of 60% of MSMEs in obtaining Business Identification Number (NIB). The synergy of these two factors substantially increases the intention and understanding of MSMEs regarding formal capital. This activity proves the effectiveness of a comprehensive approach in building the capacity of MSMEs.